E-137 Propensity adjusted comparative analysis of radial and femoral access for neurointerventional treatments. (4th August 2020) - Catapano, J; Nguyen, C; Fredrickson, V; Majmundar, N; Wilkinson, D; Baranoski, J; Cole, T; Ducruet, A; Albuquerque, F
Abstract : Background: Transradial artery (TRA) catheterization for neuroendovascular procedures is effective and associated with less complications than transfemoral procedures. However, the majority of literature for TRA is limited to series with a high proportion of diagnostic procedures as opposed to interventional treatments. The present study compares TRA and TFA approaches for cerebrovascular intervention. Methods: All patients with an endovascular intervention from 10/1/2018 to 12/31/2019 performed at a single center were retrospectively analyzed. Patients were grouped into two cohorts: those undergoing TRA and TFA access. Primary outcomes included complications and access site cross-over. Secondary outcomes analyzed were mean fluoroscopy time and contrast amount. Results: A total of 579 neurointerventional treatment procedures were performed during the 15-month study period. 163 (28%) procedures were initially attempted via a TRA and the remaining 416 (72%) via TFA. Of the 163 initially- attempted TRA procedures, 7 (4%) crossovers (4 aneurysm embolizations, 2 thrombectomies for acute stroke, and 1 AVM embolization with 6 crossing over to TFA) vs 13 (3.1%) (5 crossing over to TRA) in the TFA procedures occurred (p=0.49). Of the 162 TRA neurointerventional procedures that were carried out accounting for crossovers, 80 (35%) were for aneurysmal embolization, 31 embolization (19%) of an AVM and/or AVF, 4 (3%) thrombectomies of an acute stroke, 9 (6%) carotid artery stenting/angioplasty, 8 (5%) embolization of a tumor, 24 (15%) middle meningeal artery embolization for chronic subdural hematomas, and 6 (4%) other neurointerventions. The TRA procedures were significantly different than the 417 TFA procedures performed, which included 143 (34%) thrombectomies for acute stroke (p<0.001). A significantly greater fluoroscopy time (39 vs 30 minutes) and total contrast (156 vs 128 mL) were observed in the TRA procedures (p<0.001 for both). TFA procedures (N=43, 10%) were associated with a significantly higher complication rate than TRA procedures (N=5, 4%) (p=0.008); however, the majority of complications were mild with only 18 (3%) major complications including 3 (2%, all IPH or CVA) in the TRA procedures and 15 (3.6%; 6 IPH/CVA, 5 vessels dissections, 3 femoral occlusions, and 1 retroperitoneal bleed) in the TFA interventions. After eliminating thrombectomy patients and performing a propensity adjustment (including age, gender, symptoms, procedure, pathology, sheath and catheter size) TRA catheterization was associated with decreased odds of a complication (OR 0.25, 95% CI: 0.085–0.72, p=0.011) and a greater contrast amount (161 vs 140 mL, p=0.007), but no significant difference in fluoroscopy time (39 vs 35 minutes, p=0.052) than TFA treatments. Conclusion: TRA access for neuroendovascular interventions can be performed successfully for a variety of procedures and for numerous pathologies, with fewer overall complications and no difference in fluoroscopy times than the traditional TFA approach. Disclosures: J. Catapano: None. C. Nguyen: None. V. Fredrickson: None. N. Majmundar: None. D. Wilkinson: None. J. Baranoski: None. T. Cole: None. A. Ducruet: None. F. Albuquerque: None.